2022
DOI: 10.1007/s41810-022-00165-2
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Prediction of the Effect of Thermal Plume of a Standing Human on the Airborne Aerosol Flow in a Room: Assessment of the Social Distancing Rule

Abstract: The purpose of the study is to investigate the dispersion of droplet nuclei/aerosol which are produced during coughing and continuous talking to quantify the risk of infection due to airborne disease transmission. A three-dimensional modelling of aerosol transport due to human respiratory activities such as coughing and talking within a room environment has been simulated using CFD technique. An inert scalar transport equation was used to represent aerosol cloud, while turbulence was modelled with the $$k-\eps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…An experimental investigation [20] demonstrated that the thermal plume depended on many factors, such as body structures and types of clothing. Recently, the thermal plume generated by a person was simulated and the variation of the droplet concentration was predicted by an inert scalar equation [21]. The migration of individual droplets was not directly simulated.…”
Section: Introductionmentioning
confidence: 99%
“…An experimental investigation [20] demonstrated that the thermal plume depended on many factors, such as body structures and types of clothing. Recently, the thermal plume generated by a person was simulated and the variation of the droplet concentration was predicted by an inert scalar equation [21]. The migration of individual droplets was not directly simulated.…”
Section: Introductionmentioning
confidence: 99%